ANALISIS FINANSIAL USAHATANI GAHARU (Aquilaria malaccencis Lamk.) DI KABUPATEN SANGGAU - WUYSANG, JOYCE LINDA; GAFUR, SUTARMAN; YURISINTHAE, ERLINDA (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2015)
Agarwood (Aquilaria malaecencis lamk.) is the majority source of Non-Timber Forest Product (NTFP) in Sanggau regency. In Parindu district, Bonti district and Kapuas district have some of agarwood plantation farmer groups, that has members of 118 farmers that has been the subject of this researched. The main focus of this thesis is to understand the agarwood feasibility methods of the gaharu plantation farmer groups from the financial aspects, the return of investment (ROI) and the sensivity analysis if there were the fluctuation of regular benefit and cost of gaharu plantation.The researched found the prior cost of agarwood plantation farmer groups for seven years is Rp. 807.203.295.- and the amount of the income is Rp. 8.377.351.610.- (the income adds with the value of residual effort), from the financial analysis is found the income of NPV = Rp. 3,518,148,025.-, Net B/C ratio = 31.19 % and the IRR=102.71%, PP is 6 year 27 days that is under seven years , therefore it could be concluded that the agarwood plantation farmer groups is feasible, and the amount of the income is Rp. 8,377,351,610.- (the income without the value of residual effort), from the financial analysis is found the income of NPV = Rp. 3,480,966,096 .-, Net B/C ratio = 30,87 % and the IRR = 102.40%, PP is 6 year 28 days, therefore it could be concluded that the plantation of gaharu farmer is feasible.Sensitivity analysist for Gaharu plantation for Rp. 1.000.000,-/kg until Rp. 10.000.000,-/kg, the range of volume 0,5 kg/tree until 5 kg/tree and in the range 35% until 80% its will get NPV > 0, Net B/C ratio > 0, IRR > rate interest, and PP under planning project, so its can be concluded Agarwood plantation is feasible. Keywords: Agarwood, finansial analysis, payback period, sensitivity Sanggau